Pemberdayaan Masyarakat Melalui Program Kerja Branding UMKM Dalam Upaya Meningkatkan Ekonomi Pelaku UMKM Desa Kweden - Rena Natalia; Kharisma, Fresha; Ramadhan, Muhammad Rizky; Nihaya, Ina Uswatun (Universitas Negeri Surabaya, 2022)
Kweden village is a tourist village that is not too developed, but besides that, many of its residents work as MSME actors. Most of them learn about MSEs by self-taught through social media, especially YouTube. Due to this, many MSME actors in Kweden Village still lack knowledge of MSMEs and doing business. Many of them just go along with it in business. Therefore, the purpose of holding MSME Branding is so that MSME actors in Kweden Village can be more professional in running and developing their business which will improve the family economy and make Kweden Village better known. The method used in collecting information about the background of MSME actors is by questionnaires and interviews. And as a result, the MSME branding activity program really helps MSME actors in running their business more professionally.